Fluid simulation of ion acoustic solitary waves in electron–positron–ion plasma - Singh, Kuldeep; Kakad, Amar; Kakad, Bharati; Saini, N. S. (My University, 2021)
We performed one-dimensional fluid simulation to study the evolution and characteristics of ion acoustic solitary waves (IASWs) in a plasma comprised of hot inertial ions, superthermal electrons and positrons. The initial density perturbations in the equilibrium ion density are used to excite the IASW pulses in e–p–i plasma. This simulation illustrates the evolution of IASWs in presence of superthermal electrons and positrons. The main focus of this paper is to understand the role of positrons in the nonlinear evolution of the IASWs under the influence of ion thermal pressure. We noticed that the positron density, ion thermal pressure, superthermal index of electrons and positrons play pivotal role in the formation of IASWs. These results will be helpful in understanding the characteristics of IASWs in space/astrophysical plasmas, especially in the active galactic nucleus regions and interstellar medium where superthermal electron–positron pairs are prevalent.
Keywords: Solitory waves; Ion-Acoustic; Waves Fluid simulation; Electron positron ion plasma